Unravelling the Photoprotection Capacity of Resveratrol on Histidine Oxidation - Neyra Recky, Jael Rhode (2021)
Exposure to sun radiation causes great oxidative stress and activates a numerous of defense mechanisms in living systems, such as the synthesis of antioxidants. Resveratrol (RSV), a naturally occurring stilbene molecule, has antioxidant properties and is synthesized in large amounts when plants are under high oxidative stress. Likewise, under UV and visible radiation, biomolecules are oxidized, losing their physiological properties and, therefore, avoiding the harmful effects of solar radiation is crucial in order to preserve the functionality of cellular components. In proteins, one essential component that is often susceptible to degradation is the amino acid histidine (His), which can be modified via several oxidizing mechanisms. In this article, we evaluate the photoprotection capacity of RSV in photosensitized oxidation of His, which is initiated with a one-electron transfer reaction, yielding the His radical cation (His•+). The photoprotective properties of RSV are evaluated using kinetics analysis during steady-state irradiation and laser flash photolysis experiments. The experimental results reveal that the presence of RSV in the solution causes an evident decrease of the His consumption initial rates as a result of a reaction between His•+ and RSV that recovers the amino acid. In addition, we conclude that during its antioxidant action, RSV is consumed being a sacrificial antioxidant.